IMPLEMENTASI KEBIJAKAN PROGRAM LAYANAN RAKYAT UNTUK SERTIPIKASI TANAH (LARASITA) DI KANTOR PERTANAHAN KABUPATEN PARIGI MOUTONG PROVINSI SULAWESI TENGAH - Rahman, Saiful Rahman; Mustari, Hasanuddin; Nurhannis, Nurhannis (Katalogis, 2019)
The purpose of this study was to determine the implementation of the People's Service for Land Certification (LARASITA) program at the Land Office of Parigi Moutong Regency, Central Sulawesi Province. This type of research is descriptive, with the number of informants involved as many as 6 informants, which for determining the informants using Purposive Sampling techniques. In addition, in the data collection technique in this study through observation, interviews, documentation and literature studies. With the method of data analysis with three steps, data condensation, data display, and conclusion drawing and verification. From the results of the research, it is known that the implementation of the People's Service program for Land Certification (LARASITA) at Parigi Moutong District Office has not been carried out optimally, this can be seen after going through the research process, with many problems occurring, such as policy communication is still running at a minimum, where the distribution of all information related to the program to the target group in this case is that the community is still considered to be running less optimally. Meanwhile, from the aspect of resources it still runs less optimally, this is caused by human resource factors, the implementation of the larasita program policies in Parigi Moutong Regency is indeed in accordance with the set minimum standards of 4 people, but this number is considered less capable of accommodating all Larasita activities in a number of Subdistricts in Parigi Mouotng Regency. In addition, the condition of the resources in the form of supporting facilities for Larasita activities is considered still not feasible.